Correlation And Path Coefficient Analysis Of Some Economic Traits In Mahua (Madhuca Indica J.F. Gmel.) (Applied Biological Research, 2020)
One hundred and sixty phenotypically superior mahua (Madhuca indica)  trees from eastern Madhya Pradesh (India) were intensively assessed for  19 phenotypic traits of mahua tree, flowers and fruits. The correlation and  path coefficient of phenotypic traits were established for use in tree  improvement of this species. The flower dry weight was found positively  and significantly (p
Keywords: Correlation coefficient; mahua; path coefficient; tree improvement